Examining the indicators of the relationship between Psychological Resilience and Burnout among psychosocial counsellors who work at the prisons of the Kurdistan Region – Iraq (Raparin Journal of Humanities (RJH), 2023)
In the initial observations of the performance of prison staff, the researchers find out that psychosocial counsellors who work at the prisons face psychological stress when dealing with prisoners. The prisoners have different characteristics and personalities from individuals outside prisons due to the nature of life and dealings inside prisons. Having stress could reflect negatively on the counsellor’s work and professional performance, which may raise the possibility of exposure to psychological pressure and loss of interest in work in general, this case may consider one of the indicators of psychological combustion. The current research aims to identify the relationship between psychological resilience and burnout among psychosocial counsellors in the Kurdistan Region prisons, the research sample was 100 counsellors, (78 males and 22 females). To measure psychological resilience Holling scale (1996) developed by Maltby (2016) that included three dimensions was used. Maslach’s (1981) scale, which included three dimensions, was used to measure burnout. To analyze the data, mean, standard deviation, Cronbach alpha, one- and two-way t-test, and Pearson's correlation coefficient was used. The results show that psychosocial counsellors have high levels of psychological resilience. However, they recorded low levels of psychological burnout. In addition, resilience and burnout significantly correlated negatively. There are insignificant differences in psychological resilience depending on gender. Yet, females recorded higher levels in the field of Emotional exhaustion for burnout than males, while the differences between males and females on depersonalization, and personal accomplishment components were insignificant.